2019
DOI: 10.3897/travaux.62.e49074
|View full text |Cite
|
Sign up to set email alerts
|

Wild Pacific oyster Magallana gigas (Thunberg, 1793) populations in Romanian Black Sea waters – friend or foe?

Abstract: A relatively small population of Magallana gigas was discovered near the Agigea harbor (Constanța, Romania) in 2017. The DNA barcoding method was used to confirm the morphological identification of the species. We consider this colony to be the first instance of a possibly stable Pacific oyster population in the Black Sea, outside of farming activities. The possible impact on native ecosystems is briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Pacific oysters (C.gigas) are one of the most globalized highly commercial bivalves that have been introduced to 66 countries outside their native range (northwest Pacific) for aquaculture purposes (Herbert et al, 2016). They were first introduced to the northern Black Sea coastal waters from the Sea of Japan during the 1980s, with active attempts for its acclimatization since then (Krapal et al, 2019;Aydın and Gül, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Pacific oysters (C.gigas) are one of the most globalized highly commercial bivalves that have been introduced to 66 countries outside their native range (northwest Pacific) for aquaculture purposes (Herbert et al, 2016). They were first introduced to the northern Black Sea coastal waters from the Sea of Japan during the 1980s, with active attempts for its acclimatization since then (Krapal et al, 2019;Aydın and Gül, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In the Gulf of Trieste, which includes shores of Italy, Croatia and Slovenia, Pacific oysters have established over the whole mesolittoral and infralittoral borders and are believed to compete with the Mediterranean mussel Mytilis galloprovincialis , although no field tests were carried out 93 . In Romania, near the Agigea harbour (Constanța), a 2017 study suggested populations appeared to fill an empty ecological niche left by O. edulis , which disappeared from the Romanian coast due to predation by the invasive veined rapa whelk Rapana venosa 94 …”
Section: Resultsmentioning
confidence: 99%
“…The population was assessed at least once a year since its discovery, during diving sessions. Individuals were measured and surface of the colony assessed using the same methods described in previous studies [8].…”
mentioning
confidence: 99%